Dampak Penyederhanaan Jabatan Struktural Aparatur Sipil Negara di Institut Seni Indonesia Yogyakarta - Sutanto, Muh Heri; Triputro, R. Widodo (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research examines the impact of simplifying the structural positions of the State Civil Apparatus at the Indonesian Institute of Arts Yogyakarta. The purpose of this study is to analyze the stages of the policy process for simplifying structural positions at ISI Yogyakarta, to analyze the impacts caused by policies related to the simplification of structural positions at ISI Yogyakarta and to analyze solutions to resolve the negative impacts caused by policies related to the simplification of structural positions at ISI Yogyakarta. This type of research is descriptive with descriptive qualitative methods, the data sources used are primary and secondary, the object in this study is the Yogyakarta Institute of Arts Indonesia and the subjects in this study are the Rectorate and the structural ranks of educational staff at the Yogyakarta Institute of Arts Indonesia. The technique of determining informants is purposive technique. The data collection techniques used are observation and in-depth interviews. The data analysis techniques used are data reduction, data presentation, conclusion drawing and triangulation. The results of research on the Impact of Simplifying Structural Positions of the State Civil Apparatus are: the stages of the policy process for simplifying structural positions at ISI Yogyakarta. There are five stages of the policy process for simplifying structural positions at ISI Yogyakarta. First, identification of administrative positions in work units. Second, mapping of positions and administrative officials affected. Third, mapping functional positions that can be occupied. Fourth, alignment of functional and administrative position allowances. Fifth, the alignment of position classes refers to the rules of the Ministry of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia, 2019; The impact caused by the existence of policies related to the simplification of structural positions, First, there are differences in the characteristics of administrative positions and functional positions. Second, it hampers the career of ASN employees. Third, equalization of positions affects the position map of the relationship pattern to employee performance. Fourth, there is less opportunity for organizational refreshment with the position rotation mechanism. Fifth, equalization of positions has the opportunity to create a monotonous, linear work climate, and get stuck in a comfort zone; The solution to the problem of simplifying positions is as follows: First, identify administrative positions in work units. Second, mapping administrative positions and officials affected by simplifying the organizational structure. Third, mapping functional positions that can be occupied by officials affected by simplifying the organizational structure. Fourth, education background mapping.